Assessment of knowledge and attitude towards HIV patients among dental students in Universiti Sains Islam Malaysia (USIM) / Aws Hashim Ali Al-Kadhi ... [et al.] - Al-Kadhim, Aws Hashim Ali; Ahmad Bakri, Nurul Ainaa Syamimi; Ameruddin, Anis Mardhiya; Al-Ani, Sarah Taha Yousif; Jaafar, Azlan (Universiti Teknologi MARA Cawangan Selangor, 2019)
Introduction: Dental officers could be the first medical personal to diagnose HIV/AIDS and cross-contamination may happen. More efforts should be taken to improve knowledge and the behaviour of dental students towards HIV/AIDS patients. The objective of this study is to assess and compare knowledge and the attitude of USIM dental students towards HIV patients. Methods: A total of 136 dental students from Year 2 to Year 5 of academic year 2017/2018 participated in this study. Students were consented and briefed about the purpose of the current project prior to answering self-administered questionnaires that have been previously validated. Results: The mean total knowledge and attitude score were 69.65% (good) and 68.54(%) (passive), respectively. Both clinical and pre-clinical students have passive attitude towards HIV patients and showed good level of knowledge with 70.81% and 66.39% respectively. There were significant association between sex and knowledge of HIV/AIDS among USIM dental students (p=0.001). There is also a statistically positive weak correlation between knowledge and attitude towards HIV/AIDS patients. Conclusions: USIM dental undergraduates have good knowledge and passive attitude towards HIV/AIDS patients. Improvement of dental curriculum regarding HIV/AIDS knowledge and attitude towards HIV/AIDS patients is recommended through conducting activities such as seminar, workshop and small-group discussion among dental students.